The mobile future: how new technologies will drive success in mobile marketing - Busk, Doug (Henry Stewart Talks, 2009)
Current state of play, Market sizing, Mobile web marketing, Off-net, What is next?, Downloadables, Streaming video, Messaging, Hybrid solutions, The rise of the 'real web', Location based capabilities, Near field impact, 4G
Archived at 2022/04/11